2023
DOI: 10.1097/anc.0000000000001040
|View full text |Cite
|
Sign up to set email alerts
|

Management of Air Leaks in the Newborn

Abstract: Background: Air leaks, especially pulmonary interstitial emphysema (PIE), are increasingly uncommon respiratory complications of the newborn. Despite PIE having a decreasing incidence, it continues to have a high morbidity and mortality rate. This makes PIE one of the most severe respiratory complications to affect a newborn. Air leaks occur when there is overdistension of the terminal airways or alveoli, which results in air dissecting into extra-alveolar spaces. Recognizing the signs of air leaks is paramoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In our study, intubated patients were ventilated with significantly larger EELZ (which strongly correlates with end-expiratory lung volume) than those on non-invasive respiratory support [14]. This finding aligns with physiological principles, as the regulation of FRC under positive PEEP can be more effectively controlled through mechanical ventilation compared to non-invasive modes [15,16]. Other studies also demonstrated that respiratory support results in increased EELV over time [17].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, intubated patients were ventilated with significantly larger EELZ (which strongly correlates with end-expiratory lung volume) than those on non-invasive respiratory support [14]. This finding aligns with physiological principles, as the regulation of FRC under positive PEEP can be more effectively controlled through mechanical ventilation compared to non-invasive modes [15,16]. Other studies also demonstrated that respiratory support results in increased EELV over time [17].…”
Section: Discussionsupporting
confidence: 85%
“…Some studies also indicate that HFNC provides TV similar to CPAP [ 24 ]. Our findings of larger EELZ and DeltaZ in intubated patients could explain why mechanical ventilation is associated with higher rates of lung injury and pulmonary air leaks [ 15 , 25 , 26 ], although some data for pneumothorax rate between therapies is conflicting [ 27 ]. Nonetheless, measuring volume and distending pressures in neonates is difficult and is known to have wide interpatient as well as intrapatient variation, which also might influence observed differences [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental treatment approach for PIE involves utilizing gentle ventilation techniques to decrease barotrauma and volutrauma ( 28 ). This includes non-invasive ventilation, volume control, or high-frequency ventilation, all of which have been found effective in minimizing the development of PIE ( 8 , 29 ).…”
Section: Discussionmentioning
confidence: 99%